Child Maltreatment Fatalities Related to Inadequate Caregiver Supervision. (July 2014) - Damashek, Amy; Drass, Sabrina; Bonner, Barbara L.
More than 1, 500 children died in the United States in 2011 due to child maltreatment. A substantial portion of these deaths were due to neglect. Previous research has found that a large percentage of child neglect cases involve supervisory neglect; however, the role of inadequate caregiver supervision (ICS) in child maltreatment deaths is unknown. The present study reviewed files from the Child Death Review Board in the state of Oklahoma for the years 2000 to 2003 to examine (a) how many deaths were due to inadequate caregiver supervision and (b) which child, caregiver, family, alleged perpetrator, and incident characteristics predicted risk for death related to ICS. Results indicated that almost half of the child maltreatment deaths were related to ICS. Older children and those living in homes with greater numbers of children were more likely to die from causes related to ICS. In addition, the alleged perpetrators of deaths related to ICS were more likely to be biological parents than alleged perpetrators of non-ICS-related deaths. These findings suggest that interventions to assist caregivers in providing appropriate levels of supervision for their children may be important for reducing children's risk for death.